Filling gaps in flower fly distributions: first record of Aneriophora aureorufa (Philippi, 1865) (Diptera, Syrphidae) from Argentina - López García, Guillermo Pablo (2019)
The genus Aneriophora Stuardo & Cortés 1952, previously considered endemic to Chile, is recorded for the first time from Argentina. Specimens of Aneriophora aureorufa (Philippi, 1865) were collected in Neuquén Province and deposited in the entomological collection of the Instituto Argentino de Zonas Áridas, Mendoza, Argentina. A diagnosis, distribution map, and photographs of A. aureorufa are provided.